Medical Leadership: Formal and Informal - Dr Nadeem Ikram, Dr Nadeem Ikram (Journal of Rawalpindi Medical College, 2018)
Medical leadership is conceptualized in two ways. Physicians with formal managerial roles or physicians who act as informal ‘leader’ in daily practices. In formal leadership role, it is interchangeable with the term medical management. Informal leadership is an intrinsic component of physicians’ daily work. Here the physicians act as ‘leaders’ within their clinical role, by organizing clinical work and establishing cross-departmental collaboration. This informal role transcends formal managerial work and thus applies to all physicians. Here all are leaders in their own capacity within their own working arena.